Serum amyloid A3 deficiency impairs in vitro and in vivo adipocyte differentiation - Ellen Vercalsteren (Adipocyte, 2021)
Obesity, caused by an excess adipose tissue, is one of the biggest health-threats of the 21st century. Adipose tissue expansion occurs through two processes: (i) hypertrophy, and (ii) hyperplasia, the formation of new adipocytes, also termed adipogenesis. Recently, serum amyloid A3 (Saa3) has been implicated in adipogenesis. Therefore, the aim of this study was to investigate the effect of Saa3 on adipogenesis using both an in vitro and in vivo murine model. Saa3 gene silenced pre-adipocytes ha a lower expression of pro-adipogenic markers and less lipid accumulation, indicating impaired adipogenesis. Furthermore, male NUDE mice, injected with Saa3 gene silenced pre-adipocytes developed smaller fat pads with smaller adipocytes and lower expression of pro-adipogenic markers than their control counterparts. This confirms that Saa3 gene silencing indeed impairs adipogenesis, both in vitro and in vivo. These results indicate a clear role for Saa3 in adipogenesis and open new perspectives in the battle against obesity.